Long-term hormonal therapy resulting in breast cancer in female-to-male transsexual: Case report - Treskova, Inka; Hes, Ondrej; Bursa, Vlastimil (Medicine, 2018)
RATIONALE: Testosterone is important for the development of secondary sexual characteristics in female-to-male transsexuals. On the contrary, it can increase the risk of breast cancer. PATIENT CONCERNS: We present a rare case of breast cancer in female-to-male transsexual patient after long-term hormonal therapy. DIAGNOSIS: Breast cancer in female-to-male transsexual patient. INTERVENTIONS: The patient underwent mastectomy and chemotherapy. OUTCOMES: The patient had local recurrence of the disease and he underwent re-excision, radiotherapy and the tamoxifen treatment. After this treatment, the patient is in the remission from the disease. LESSONS: Breast cancer in transsexuals appears to be rare. However, there is a potential risk that testosterone exposure can increase the risk of developing breast cancer by the stimulation of breast tissue. There is limited published literature on the risk of breast cancer in transsexual patients.
Keywords: Female; Hormone Replacement Therapy; Long Term Adverse Effects; Testosterone; hormonální substituční terapie; nádory prsu; lidé; testosteron; Middle Aged; Breast Neoplasms; Humans; ženské pohlaví; lidé středního věku; Male; Transsexualism; transsexualismus; dlouhodobé vedlejší účinky; mužské pohlaví